RESOLUSI KONFLIK BERBASIS ADAT Studi Resolusi Konflik Harta Pusaka Tinggi di Nagari Gantuang Ciri, Kab. Solok, Sumatera Barat - Yuhelna . (Jurnal Ilmu Sosial Mamangan, 2014)
Conflict of harta pusaka tinggi is a kind of conflict often occurs in Minangkabau. The Court of Sumatera Barat issued a circular to solve ‘sako’ and ‘pusako’ conflict by custom mechanism. This article explain harta pusaka tinggi conflict resolution base on institution Minangkabau custom mechanism and effectiveness. Specifically this article explain step and mechanism of conflict resolution of harta pusaka tinggi base on institution of Minangkabau custom and effectiveness to solve harta pusaka tinggi problem.